What Are Residents Paying Attention To? An Exploration of Mind Wandering During Classroom-Based Teaching Sessions (Academic Half-Days) in Postgraduate Medical Education - Acai, Anita (My University, 2016)
INTRODUCTION: Academic half-days (AHDs) are regular teaching events that occur outside of patient care. AHDs often take the form of extended didactic lectures, despite the literature around effective teaching techniques. This may decrease residents’ ability to pay attention to the content being presented and instead promote mind wandering (defined in this thesis as self-reported task-unrelated thought). This thesis examines mind wandering during academic half-days (AHDs) in postgraduate medical training through two studies, with the overarching goal of understanding how results might inform the design of classroom-based teaching sessions in postgraduate medical education. METHODS: In the first study, a qualitative approach was used to examine residents’ perceptions about the nature of their learning experience during AHDs. Two focus groups were held with residents in hematology (n = 5) and obstetrics and gynecology (n = 15) and analyzed using a thematic analysis approach. In the second study, thought probes were administered approximately every 15 minutes during three AHD sessions in each program (hematology: n = 6 residents; obstetrics and gynecology: n = 30 residents) to quantitatively examine how three commonly-used instructional methods (didactic lecture, group discussion, and case-based learning) influenced mind wandering during AHDs. RESULTS: Findings of the qualitative study revealed differences with respect to residents’ overall perceptions of AHDs, perceptions of attention during AHDs, and motivations for learning. However, residents in both programs agreed that presenters could maximize resident engagement and learning by spending more time on case-based learning and group discussions as opposed to didactic lectures. Quantitative findings supported resident perceptions, demonstrating significantly less mind wandering during case-based learning (7%) than didactic lectures (33%). CONCLUSIONS: The findings of this work suggest that instructional method influences the amount of self-reported mind wandering during AHDs, and specifically, that case-based learning may be more effective than didactic lectures in maintaining engagement during AHDs.
Keywords: academic half-days; mind wandering; attention; classroom learning; postgraduate medical education; resident training